ANALISIS PENGARUH UKURAN DEWAN KOMISARIS, KOMITE AUDIT, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Pada Perusahaan Yang Terdaftar Di Bei Periode 2013-2015) - Pratama, Alvin Akbar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study assesses the influence of size of board of commissioners, audit committee, managerial ownership, institutional ownership, and company size on dividend policy. This descriptive research uses quantitative approach. The sample was taken from the entire companies listed in the Indonesia Stock Exchange from the year of 2013 to 2015 using purposive sampling method. The analysis is multiple linear regression processed using SPSS. The result shows that size of board of commissioners, managerial ownership, and size of company influence dividend policy. However, audit committee and institutional ownership do notinfluence it.Keywords: good corporate, dividend payout ratio (DPR)